Characterization of the complete chloroplast genome of Punica granatum 'Luqing1'. Issue 3 (2nd July 2020) - Feng, Lijuan; Yang, Xuemei; Jiao, Qiqing; Wang, Chuanzeng; Yin, Yanlei; Tao, Jihan
Abstract: Punica granatum 'Luqing1' is an important d fruit tree with high quality and strong cold-resistance. The complete chloroplast genome (Accession: MN630638) was sequenced, assembled, and annotated. The size of chloroplast genome was 158, 638 bp with large single-copy (LSC, 89, 021 bp) regions, small single-copy (SSC, 18, 685 bp) regions, and two inverted repeat regions (IRs, 25, 466 bp each). A total of 130 genes were successfully annotated, including 85 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The phylogenetic relationships showed that P. granatum 'Luqing1' was closely related with different pomegranate cultivars.